Design exemplars for synchronous e-learning: A design theory approach - Hrastinski, Stefan; Keller, Christina; Carlsson, Sven A. (Computers and education, 2010)
Synchronous e-learning has received much less research attention, as compared with asynchronous e-learning. Practitioners that consider using and designing synchronous e-learning are in urgent need of guidance. In order to address this need, we propose design exemplars for synchronous e-learning. They are directed towards a primary constituent community of teachers, administrators, managers and developers of e-learning. The exemplars have been theoretically as well as empirically grounded through cross-case analyses of studies conducted between 2003 and 2006. Moreover, the exemplars have been evaluated by conducting focus group sessions with experienced practitioners having experience of using and developing e-learning. Strong support was identified for each design exemplar. The exemplars can be used as research hypotheses and be tested in future design research.